METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VB PADA MATA PELAJARAN IPS DI SDN 002 BAGAN BESAR KECAMATAN BUKIT KAPUR KOTA DUMAI - Dewi Anggraini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2015)
The background of this study is the teaching and learning process in the classroom VB SDN 002 Bagan Besar, Dumai in social studies that are still dominated by teachers so that students become passive blindly accept the material provided by the teacher and the learning outcomes are not satisfactory with an average value below KKM. This study aims to determine whether there is influence of the method of discussion, both individually and classically on learning outcomes in the VB class IPS Subjects in SDN 002 Bagan Besa Kecamatan Bukit Kapur, Dumai. The study was conducted for 32 students consisting of 20 men and 12 women. Data were collected through observation by the observer uses observation sheets to the data the method of discussion, and through postes unutuk learning outcomes data. The results showed that the method of discussion individually significant influence on student learning outcomes. Where 28 people declared complete their study of 32 students. Seen in the classical, was the method of discussion is also a significant influence, namely the classical completeness gain of 87.53%, with an average score 75.31. This means that the discussion method can improve student learning outcomes either individually or classical.Keywords: methods of discussion, social studies learning outcomes